Tree diversity regulates forest pest invasion - Guo, Qinfeng; Fei, Songlin; Potter, Kevin M; Liebhold, Andrew M; Wen, Jun (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Nonnative pests often cause cascading ecological impacts, leading to detrimental socioeconomic consequences; however, how plant diversity may influence insect and disease invasions remains unclear. High species diversity in host communities may promote pest invasions by providing more niches (i.e., facilitation), but it can also diminish invasion success because low host dominance may make it more difficult for pests to establish (i.e., dilution). Most studies to date have focused on small-scale, experimental, or individual pest/disease species, while large-scale empirical studies, especially in natural ecosystems, are extremely rare. Using subcontinental-level data, we examined the role of tree diversity on pest invasion across the conterminous United States and found that the tree-pest diversity relationships are hump-shaped. Pest diversity increases with tree diversity at low tree diversity (because of facilitation or amplification) and is reduced at higher tree diversity (as a result of dilution). Thus, tree diversity likely regulates forest pest invasion through both facilitation and dilution that operate simultaneously, but their relative strengths vary with overall diversity. Our findings suggest the role of native species diversity in regulating nonnative pest invasions.
Keywords: Biodiversity; Insecta; biotic resistance; Host-Parasite Interactions; interakce hostitele a parazita; Forests; facilitation; biodiverzita; Models, Biological; constraint envelope; Animals; United States; biologické modely; hmyz; zvířata; Spojené státy americké; lesy; dilution; host vs. nonhost